(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research aims to study the definition of the crime of unauthorized access to information systems and to highlight the efforts of the Kingdom of Saudi Arabia in combating it. Since this crime is closely related to cybercrimes, and given the novelty and significant evolution of cybercrimes in the modern era with the development and spread of the Internet, the threat of cybercrimes in various forms and types has increased. This has led to a concerted international effort to combat these crimes and address their infiltration and spread in all countries of the world. The Kingdom of Saudi Arabia has made intensive efforts to combat cybercrimes and has worked on developing legislative systems to keep pace with methods of combating all cybercrimes. The study adopted an analytical approach to the texts of the Saudi Anti-Cyber Crime Law, as well as a comparative approach to similar laws and legislative systems, aiming to reach conclusions and recommendations related to the study. The research addressed the extent of the development of legislative systems and the efforts made to combat cybercrimes at the international level in general and in the Kingdom of Saudi Arabia in particular. The research then discussed the definition of the crime of unauthorized access to information systems by dividing the study into two main sections. The first section focused on the development of legislative systems in combating cybercrimes, which the study addressed through two subsections: the first subsection provided an overview of international efforts to combat cybercrimes, and the second subsection discussed the development of the efforts of the Kingdom of Saudi Arabia in combating cybercrimes. The second section dealt with the definition of the crime of unauthorized access to information systems, divided into two subsections: the first subsection covered the concept and philosophy of the crime of unauthorized access to information systems, and the second subsection distinguished between the crime of unauthorized access and related offenses.